Styrene Copolymerization Using a Metallocenic Initiator. Homo- and Copolymerization of Styrene with Isoprene Through Zirconocene-Mao Initiating Systems - Rabagliati-Canessa, F; Muñoz-Moena, L; Muñoz-Moena, L (2011)
The copolymerization of styrene with isoprene (Ip) has been tested using combined zirconocene-methylaluminoxane (MAO) initiating system. Both halfsandwich and real zirconium-based metallocenes were used. Regardless of the metallocene employed, conversion to copolymer was much influenced by the proportion of Ip in the initial feed. As the proportion of Ip is enriched, conversion to copolymer decreases substantially. Results of NMR and DSC analyses indicate that the products obtained were truly copolymers and not a mixture of both homopolymers. The studied zirconocene-MAO initiating system produces atactic polystyrene. A small amount of Ip in the initial feed substantially diminishes the conversion and at best traces of poly(isoprene) were detected in the homopolymerization of Ip with these initiating systems. © Springer-Verlag 2011.